2010
DOI: 10.1074/jbc.m110.104430
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of the Base Excision Repair Pathway by BRCA1

Abstract: Inactivation of the breast cancer susceptibility gene BRCA1 plays a significant role in the development of a subset of breast cancers, although the major tumor suppressor function of this gene remains unclear. Previously, we showed that BRCA1 induces antioxidant-response gene expression and protects cells against oxidative stress. We now report that BRCA1 stimulates the base excision repair pathway, a major mechanism for the repair of oxidized DNA, by stimulating the activity of key base excision repair (BER) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 48 publications
2
82
0
Order By: Relevance
“…29,30 Cell survivability was measured as described under 'Methods.' Overexpression of LAMP2A, in both MCF-7 and T47D cells, induced cell survivability approximately by 15-20%, when compared with background vector and vehicle ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…29,30 Cell survivability was measured as described under 'Methods.' Overexpression of LAMP2A, in both MCF-7 and T47D cells, induced cell survivability approximately by 15-20%, when compared with background vector and vehicle ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MCF-7 and T47D human mammary adenocarcinoma cell lines were obtained from the American Type Culture Collection (ATCC, HTB-22, HTB-133) and cultured as described previously. 30 MCF-7 cells were isolated from a 69-y-old Caucasian woman suffering from invasive breast ductal carcinoma. This epithelial lineage cell line has wild-type TP53, posseses both estrogen and progesterone receptors and is only tumorigenic in mice if supplemented with estrogen.…”
Section: Patient Tissue Blot Oncopair Insta-blotmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified a common motif (AACGTAA) in both mouse and human fragments that are potentially responsive to OCT1, a wellstudied transcription factor ( Figure 6A). Previous investigations indicated that BRCA1 and OCT1 interact with each other and regulate downstream gene expression through binding to the OCT1 consensus sequence [42], and Oct1 deficiency impairs transcriptional activity of BRCA1 [43]. Next, we performed following experiments to investigate whether the regulation of DNMT1 by BR-CA1 is indeed mediated by the OCT1 consensus site.…”
Section: Brca1 Binds To the Dnmt1 Promoter Through A Potential Oct1 Smentioning
confidence: 99%